Meta-Analysis of the Clinical Efficacy of Thalidomide Combined With Traditional Chinese Medicine in the Treatment of Behcet's Disease - Kwun Kit Hung; Syu Yiu Michelle Ng; Sai Hei Fang; Yan Ting Ip (Medicine Insights, 2026)
To systematically evaluate the clinical efficacy of thalidomide combined with traditional Chinese medicine (TCM), compared with monotherapy (either thalidomide or TCM monotherapy), in patients with Behçet's disease, and to perform a meta‐analysis. Randomized controlled trials (RCTs) published from the inception of the databases to August 1, 2026, were systematically searched in the China National Knowledge Infrastructure (CNKI), Wanfang Data, VIP Database, PubMed, Web of Science, and Cochrane Library. Patients in the control groups received conventional thalidomide therapy, whereas those in the treatment groups received TCM in addition to conventional thalidomide therapy. A meta-analysis was performed to comprehensively evaluate the clinical efficacy of the two treatment approaches. A total of 10 studies were included in the meta-analysis. The pooled results showed that the clinical efficacy was significantly higher in the treatment group than in the control group (OR = 4.96, 95% CI: 2.78–8.83, P < 0.00001), with a statistically significant difference. Compared with conventional thalidomide therapy alone, thalidomide combined with TCM appears to be more effective in the treatment of Behçet's disease.